2018
DOI: 10.1155/2018/4030689
|View full text |Cite
|
Sign up to set email alerts
|

How Slight Solidification Rate Variations within Cast Plate Affect Mechanical Response: A Study on As‐Cast A356 Alloy with Cu Additions

Abstract: e present work investigates a narrow range of secondary dendrite arm spacing (SDAS), in an as-cast A356 alloy with and without copper (Cu) additions. Cu was added to the base A356 alloy melt to reach the target concentration of 0.5 and 1 wt.%. Samples were selected from 3 different positions within the cast plate, offering 30, 35, and 40 μm SDAS variants. Tensile curves revealed a strong influence between the specimen cutting position and strength, with a pronounced effect in the Cu-containing alloys. Hardness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The percentage increase of YS was comparable to the results reported by Seifeddine et al [6] , who investigated alloys with chemical compositions, modification treatments, and solidification conditions similar to those described in the present work. Moreover, a drop in UTS occurs for samples with a Cu content of 3.2 wt%, whereas other authors reported this drop at lower Cu contents of around 1.5-2 wt% [3][4][5][6][7] . The increased quantity of Q and 𝜃 phases in Alloy Cu 3.0 was responsible for this significant drop in UTS and elongation, as highlighted by the analysis of fracture profiles and surfaces ( Fig.…”
Section: Microstructural and Mechanical Propertiesmentioning
confidence: 80%
See 2 more Smart Citations
“…The percentage increase of YS was comparable to the results reported by Seifeddine et al [6] , who investigated alloys with chemical compositions, modification treatments, and solidification conditions similar to those described in the present work. Moreover, a drop in UTS occurs for samples with a Cu content of 3.2 wt%, whereas other authors reported this drop at lower Cu contents of around 1.5-2 wt% [3][4][5][6][7] . The increased quantity of Q and 𝜃 phases in Alloy Cu 3.0 was responsible for this significant drop in UTS and elongation, as highlighted by the analysis of fracture profiles and surfaces ( Fig.…”
Section: Microstructural and Mechanical Propertiesmentioning
confidence: 80%
“…As the investigated specimens were directionally solidified, the mechanical properties were beneficially influenced by Cu contents of greater than 1.5 wt%. Di Giovanni et al [7] observed an increase in the range of 25-30% for UTS with 1 wt% of Cu content, for SDAS going from 30 to 40 𝜇m.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This was due to the nature of the analysis, which also analysed the background of the sample. The phases were determined on the basis of EDS analyses and previous reports [17,18,[20][21][22][23].…”
Section: Metallographymentioning
confidence: 99%